2010
DOI: 10.1103/physrevlett.104.047002
|View full text |Cite
|
Sign up to set email alerts
|

Gutzwiller Density Functional Studies of FeAs-Based Superconductors: Structure Optimization and Evidence for a Three-Dimensional Fermi Surface

Abstract: The electronic structures of FeAs compounds are sensitive to FeAs bonding, which is described unsuccessfully by the local density approximation (LDA). Treating the multiorbital fluctuations from ab inito LDA+Gutzwiller method, we can now predict the correct FeAs bond length and bonding strength, which will explain the observed "soft phonon." The bands are narrowed by a factor of 2 from their LDA widths. The d{3z{2}-r{2}} orbital is pushed up to cross the Fermi level, forming a three-dimensional Fermi surface, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 46 publications
7
81
0
Order By: Relevance
“…The absence of Josephson plasma edge could be taken as an indication that the 122 iron-pnictides are quasi 3D systems with the presence of dispersive band along the c-axis. Presence of 3D Fermi surfaces (FSs) was also suggested from band structure calculations 22 and a number of other experimental probes. [23][24][25][26][27] In particular, recent ab-initio LDA+Gutzwiller calculations, where electron correlations are taken into account beyond LDA, indicated that the large-size 3D ellipsoid like FS has a dominant Fe-3d 3z 2 −r 2 orbital characteristic 22 .…”
Section: Resultsmentioning
confidence: 99%
“…The absence of Josephson plasma edge could be taken as an indication that the 122 iron-pnictides are quasi 3D systems with the presence of dispersive band along the c-axis. Presence of 3D Fermi surfaces (FSs) was also suggested from band structure calculations 22 and a number of other experimental probes. [23][24][25][26][27] In particular, recent ab-initio LDA+Gutzwiller calculations, where electron correlations are taken into account beyond LDA, indicated that the large-size 3D ellipsoid like FS has a dominant Fe-3d 3z 2 −r 2 orbital characteristic 22 .…”
Section: Resultsmentioning
confidence: 99%
“…[20]. The GA approximation was, thereafter, extensively developed [21][22][23][24][25][26][27], and it has been formulated and implemented in combination with realistic electronic structure calculations such as the LDA þ GA approach [23,28], which has been applied successfully to many systems [29][30][31][32][33][34][35][36]. A third important many-body technique is the slave boson approach (SB) [37,38], which is, in principle, an exact reformulation of the quantum many-body problem for model Hamiltonians, and it reproduces the results of the GA at the saddle-point level [24,39].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [11][12][13][14][15][16][17][18]), and its combination with dynamical mean field theory (LDA+DMFT) [19][20][21][22][23][24][25] is nowadays the state-of-the-art ab initio many-body approach to low-energy properties of transition metal pnictides. Despite tremendous successes, however, limitations have also been pointed out e.g.…”
mentioning
confidence: 99%